2019
DOI: 10.1016/j.envpol.2019.04.115
|View full text |Cite
|
Sign up to set email alerts
|

Does salinity modulates the response of Mytilus galloprovincialis exposed to triclosan and diclofenac?

Abstract: In the present study Mytilus galloprovincialis mussels were exposed for days to three salinities: 30 (control), 25 and 35. Simultaneously, organisms at each salinity were exposed to either the antimicrobial agent Triclosan (TCS) or the pharmaceutical drug Diclofenac (DIC) at 1 µg/L. Salinity alone and exposure to PPCPs exposures changed mussel's metabolic capacity and oxidative status, but no additive or synergetic effects resulting from the combined exposure to different stressors were observed. Overall the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…However, this response may occur up to certain stress levels, after which organisms have the need to use their energy reserves. Also studies conducted by Freitas et al (2019c) demonstrated that M. galloprovincialis specimens exposed to different salinities increased their GLY content under stressful salinity conditions (25 and 35). Marigómez et al (2017) also showed that, in comparison with healthy mussels, stressed populations showed a high energy storage that partially contributes to alleviate thermal stress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this response may occur up to certain stress levels, after which organisms have the need to use their energy reserves. Also studies conducted by Freitas et al (2019c) demonstrated that M. galloprovincialis specimens exposed to different salinities increased their GLY content under stressful salinity conditions (25 and 35). Marigómez et al (2017) also showed that, in comparison with healthy mussels, stressed populations showed a high energy storage that partially contributes to alleviate thermal stress.…”
Section: Discussionmentioning
confidence: 96%
“…When subjected to environmental changes, such as increases/decreases in salinity and/or the presence of pollutants, organisms often increase their ROS formation with consequent changes on their antioxidant mechanisms of defence. Previous studies already demonstrated that the presence of pollutants such as pharmaceuticals but also changes on salinity levels may induce oxidative stress in marine invertebrates, with alteration on antioxidant enzymes activities, occurrence of cellular damage and loss of redox balance (among others, Franzellitti et al, 2013;Zuccato et al, 2006;Gonzalez-Rey, et al, 2014;Freitas et al, 2019bFreitas et al, , 2019c. In the particular case of SA, previous studies already described increases of antioxidant enzymes and lipid peroxidation levels, suggesting its potential pro-oxidative effect (Doi et al 2002;Doi and Horie 2010), also in non-target organisms (Nunes et al, 2015;Freitas et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Such findings may indicate that by increasing their metabolism mussels were J o u r n a l P r e -p r o o f Journal Pre-proof trying fuel up and activate their defense mechanisms to fight against the stress induced by SLS but at the highest concentration this capacity was no longer effective. Other studies revealed similar patterns, with organisms presenting an increasing metabolic capacity along the increasing exposure concentration gradient (De Marchi et al, 2017a, b) while at highly stressful conditions organisms metabolic capacity decreased (Freitas et al, , 2019Pinto et al, 2019), indicating that organisms may have limit capacity to continuously increase their metabolic capacity if stress conditions exced their tolerance limits.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 58%
“…However, recent studies pointed out that toxic effects of SLS may be related to the disruption of the osmotic balance and induction of oxidative stress, as demonstrated by Messina et al (2014) and Nunes et al (2008). It has been shown that oxidative stress is induced by a wide variety of pollutants, with published studies revealing the impacts of a wide diversity of pharmaceuticals and PCPs (PPCPs), including surfactants, on marine species oxidative stress performnce (among others, Almeida et al, 2015;Freitas et al, 2019;Messina et al, 2014;Nunes et al, 2005;Nunes et al, 2008). Among the biomarkers most widely measured as a consequence of PPCPs exposure are: i) lipid peroxidation (LPO), which reveal injuries at a cellular level caused by the overproduction of reactive species (ROS); ii) activity of antioxidant enzymes, corresponding to organisms defense mechanisms to J o u r n a l P r e -p r o o f Journal Pre-proof eliminate the excess of ROS; and iii) content of reduced glutathione (GSH) that considered to be one of the most important scavengers of ROS, and its ratio with oxidised glutathione (GSSG) may be used as a marker of oxidative stress.…”
Section: J O U R N a L P R E -P R O O F Journal Pre-proofmentioning
confidence: 99%
“…Both under laboratory and field conditions, impacts of pharmaceutical drugs on marine bivalves have been reported, from molecular changes to the organism level (Fabbri and Franzellitti, 2016;Martínez-Morcillo et al, 2020). Mortality and changes in growth, reproduction, and behavior alterations, at the individual level, as well as changes on physiological, cellular and molecular responses (e.g., immunological, antioxidant, detoxification, neurological and metabolism parameters) at the sub-individual level, were observed in marine bivalves exposed to pharmaceutical drugs under field (e.g., Martínez-Morcillo et al, 2020) but mainly laboratory conditions (Balbi et al, 2021(Balbi et al, , 2018Fabbri and Franzellitti, 2016;Freitas et al, 2019;Gonzalez-Rey and Bebianno, 2014;Honkoop et al, 1999;Lacaze et al, 2015;Martin-Diaz et al, 2009;Solé et al, 2010). Pharmaceuticals as carbamazepine (CBZ, antiepileptic drug) and cetirizine (CTZ, antihistaminic drug) have been found in the ng/L range in the marine environment, although higher concentrations (µg/L range) were determined in freshwater ecosystems (e.g., Bahlmann et al, 2014Bahlmann et al, , 2012Bahlmann et al, , 2009Brumovskỳ et al, 2016;Calisto et al, 2011;Čelić et al, 2019;Ebele et al, 2017;Nödler et al, 2014;Rehrl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%